Contact Stress Analysis of Spur Gears and Performance Evaluation in Oat flake Rolling Machine - Ko Ko, Chit; Win, Htay Htay; Swe, War War Min; Soe, Aung Kyaw (AI Society & STMIK Indonesia, 2024)
This paper focuses on examining the structural integrity of spur gears within an oat flaking machine. This machine functions by compressing oat grains situated between a pair of horizontally aligned rollers. These rollers, set to revolve at a speed of 400 rpm and a gap of 0.45 mm, process the grains into flakes. The rotation of the rollers is facilitated by spur gears, which are propelled by a belt drive connected to an electric motor. Following a fractional rotation, the processed oats are ejected as flakes. The power transmission between gears occurs through the interaction of meshing teeth. The contact stress on the spur gear is determined using Hertz's theory, and the analysis of contact stress across two meshing spur gear teeth is executed with varying number of gear teeth via ANSYS software. The findings are delineated, and the results from finite element analysis simulations are juxtaposed with theoretical calculations. The theoretical values for effective stress and strain in contact stress analysis are 60.75 MPa and 0.51309×10⁻⁴, respectively, while simulation values are 61.78 MPa and 6.1846×10⁻⁴. Theoretical and simulation results are nearly the same. Therefore, the design is safe for oat flake rolling machine. The machine's performance was tested with 0.45 mm and 0.6 mm flakes over three days. For 0.45 mm flakes, the average capacity was 28.99 kg/hr with 99.46% efficiency, while for 0.6 mm flakes, it was 48.14 kg/hr with 99.73% efficiency. These results confirm that the machine operates reliably and efficiently at both settings.